The Potential of Lavender Aromatherapy in Reducing Anxiety Levels of Patients' Families in the ICU Room at Ulin Regional Hospital Banjarmasin - Puteri, Assyifa Lutfia; Nasution, Tina Handayani; Pertiwiwati, Endang (Universitas Padjadjaran, 2025)
Anxiety is a common issue experienced by families in the ICU and can negatively impact decision-making regarding patient care. One therapy that can help alleviate anxiety is aromatherapy. Aromatherapy is a non-pharmacological therapy known to reduce anxiety. Lavender contains compounds that can help relieve anxiety. Inhalation aromatherapy using lavender essential oil can influence anxiety levels. The purpose of this study is to determine the potential of lavender aromatherapy in reducing the anxiety levels of patients’ families in the ICU at Ulin Regional Hospital Banjarmasin. This study used a quasi-experimental pretest-posttest design with consecutive sampling involving 30 family members of patients in the ICU at Ulin Regional Hospital Banjarmasin. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and analyzed using the Wilcoxon test. The results showed a significant difference in anxiety levels before and after the administration of lavender aromatherapy, with a p-value of 0.000, indicating that post-test scores were lower than pre-test scores. In conclusion, lavender aromatherapy has the potential to reduce the anxiety scores of patients' families in the ICU at Ulin Regional Hospital Banjarmasin. Therefore, lavender aromatherapy could be considered as an alternative method to help lower anxiety levels among family members. Keywords: Aromatherapy, anxiety, family, ICU.